New edge of antibiotic development: antimicrobial peptides and corresponding resistance - Nadia S. Parachin (Frontiers Research Topics, 2014)
Antimicrobial peptides, commonly isolated from several organisms, have been considered part of innate immune system and also as potential antimicrobial drugs. Besides its antimicrobial activity, some AMPs also have antifungal activity, inmmunomodulatory and antitumural activities. Lately not only nature has become a source of AMPs. Besides isolation of natural organisms, antimicrobial peptides might be improved or created using computational tools. This opens even more this so amazing field by creating infinite novel and remarkable possibilities. Overall the current issue highlights the relevance of such Research Topic with perspectives to develop entirely new molecules with vast application within health and agricultural field with higher affinity for its target with concomitant reduction of side effects.